Complementary angles sum up to 90 degrees. Let's denote the measures of the two angles as:
\[ \text{First angle} = 36^\circ \] \[ \text{Second angle} = x - 3 \]
Since they are complementary, we can write the equation:
\[ 36 + (x - 3) = 90 \]
Now, simplify the equation:
\[ 36 + x - 3 = 90 \] \[ x + 33 = 90 \]
Next, isolate \(x\) by subtracting 33 from both sides:
\[ x = 90 - 33 \] \[ x = 57 \]
Now, we can find the measure of the unknown angle:
\[ \text{Unknown angle measure} = x - 3 = 57 - 3 = 54 \]
So, the final answers are:
\[ x = 57, \quad \text{unknown angle measure} = 54 \]